1971
DOI: 10.1063/1.1659885
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectra and Intensities of Nd3+ in YAlO3

Abstract: The optical absorption and emission spectra, fluorescence kinetics, and radiative and nonradiative transition probabilities of Nd3+ ions in YAlO3 are investigated. Measurements are presented of the energy levels, absorption and emission cross sections, linewidths as a function of temperature and Nd concentration, thermal line shifts, and fluorescence branching ratios. Judd-Ofelt intensity parameters for electric-dipole transition probabilities are derived from measurements of the absorption spectrum. Stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…To our knowledge, most of the research results are focused on the crystal growth [5], unpolarized spectra under different annealing conditions [6] and laser output properties [7][8][9][10][11][12]. However, the anisotropy of Tm:YAP has been rarely reported, compared to that of Nd:YAP crystals [13][14][15]. Therefore, it is necessary to study the anisotropy characteristic of Tm:YAP crystal for its further application.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, most of the research results are focused on the crystal growth [5], unpolarized spectra under different annealing conditions [6] and laser output properties [7][8][9][10][11][12]. However, the anisotropy of Tm:YAP has been rarely reported, compared to that of Nd:YAP crystals [13][14][15]. Therefore, it is necessary to study the anisotropy characteristic of Tm:YAP crystal for its further application.…”
Section: Introductionmentioning
confidence: 93%
“…As we know, when narrow-band or line source such as light-emitting diodes or krypton arc lamps are used for optical pumping, the exact location and strength of individual absorption lines are of importance [14]. In YAP crystal, because of the anisotropy, these absorption intensities vary with orientation.…”
Section: Absorption Spectramentioning
confidence: 99%
“…Its anisotropy and the nature birefringence features make YAP be an excellent host crystal for laser applications [6]. Although previous results showed that Yb:YAP crystal has a little higher pump power than that of Yb:YAG [2], however, Yb:YAP crystal can produce linearly polarized lasers, which makes it a potentially useful laser gain medium in a variety of nonlinear laser-diode pumped solid-state configurations.…”
Section: Introductionmentioning
confidence: 98%
“…The Judd-Ofelt theory, widely used to analyse the forced electric dipole transitions within the 4f n configuration of the rare earth ions and extensively introduced in the literature [19][20][21][22][23] (Figure 2).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%